2019
DOI: 10.4047/jap.2019.11.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Color changes of ceramic veneers following glazing with respect to their composition

Abstract: PURPOSE The purpose of this study was to compare the translucency and color changes of ceramic laminate veneers of different composition following glazing process. MATERIALS AND METHODS 10 mm × 10 mm square specimens of 0.6 mm and 1.0 mm thicknesses were fabricated with IPS e.max Press (EM) and IPS e.max ZirPress (ZP) (n=10 per group). The color coordinates (CIE L * a * b * ) of the specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…The change in the optical properties of this ceramic material was attributed also to the loss of the glaze in some of the restorations. A recent study has reported that glazing increases the translucency of lithium disilicate ceramics and also affects the color, becoming darker with a color change in the green–yellow direction [ 56 ]. Accordingly, in the present study, in the 1-year recall, the IPS e.max CAD onlays that lost the glaze, and showed a distinct deviation in color and translucency, were more opaque and brighter.…”
Section: Discussionmentioning
confidence: 99%
“…The change in the optical properties of this ceramic material was attributed also to the loss of the glaze in some of the restorations. A recent study has reported that glazing increases the translucency of lithium disilicate ceramics and also affects the color, becoming darker with a color change in the green–yellow direction [ 56 ]. Accordingly, in the present study, in the 1-year recall, the IPS e.max CAD onlays that lost the glaze, and showed a distinct deviation in color and translucency, were more opaque and brighter.…”
Section: Discussionmentioning
confidence: 99%
“…Color stability is an important esthetic parameter for metal free all ceramic restorations (27) . The susceptability of color changes after repeated firing and its effect on microstructure has gained great interest in several studies (26)(27)(28)(29)(30)(31)(32) .…”
Section: Discussionmentioning
confidence: 99%
“…According to previous Studies, ΔE value of 1 represents a color change perceivable by 50% of obervers under controlled conditions (37,38,39) . A ΔE value of 2.72 represents a change perceivable by ordinary observers or patients (40) , however, the clinically permitted ΔE value is between ≤3.3 andΔE ≤ 3.7 (28) . Based on such literature, For both IPS e.max press and Celtra press, there was no statistically significant difference between mean ΔE at different firing cycles except from the first to third firing cycles (P<0.5).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional ceramic colored glaze often adds different metal ions according to the need of color such as adding copper ions to show red, adding cobalt ions to appear blue, [1][2][3][4][5] which will lead to the introduction of toxic and harmful ingredients and an increase of the production cost. [6][7][8][9] Simultaneously, some ceramic colored glazes face immense difficult problems by virtue of complex ingredients, different sintering atmospheres or temperatures and other factors, which strongly impacts the color of products. In this context, photonic crystals, as a kind of optical structure material which arranges dielectric materials with different permittivities periodically in space, [10][11][12][13] are fundamentally characterized by the existence of a photonic band gap, which prevents photons from entering photons to produce structural color.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional ceramic colored glaze often adds different metal ions according to the need of color such as adding copper ions to show red, adding cobalt ions to appear blue, [1–5] which will lead to the introduction of toxic and harmful ingredients and an increase of the production cost [6–9] . Simultaneously, some ceramic colored glazes face immense difficult problems by virtue of complex ingredients, different sintering atmospheres or temperatures and other factors, which strongly impacts the color of products.…”
Section: Introductionmentioning
confidence: 99%